2020
DOI: 10.1093/jas/skaa271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mineral methionine hydroxy analog chelate in sow diets on epigenetic modification and growth of progeny

Abstract: The study was conducted to determine the effects of mineral methionine hydroxy analogue chelate (MMHAC) partially replacing inorganic trace minerals in sow diets on epigenetic and transcriptional changes in muscle and jejunum of progeny. The MMHAC is zinc (Zn), manganese (Mn), and copper (Cu) chelated with methionine hydroxy analogue (Zn-, Mn-, and Cu-MHAC). On d 35 of gestation, 60 pregnant sows were allotted to 2 dietary treatments in a randomized completed block design using parity as a block: (1) ITM: inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Thus, crypt cell proliferation has been used as a marker showing the status of intestinal maturation, development, or maintenance of pigs. According to Jang et al [88], the proportion of proliferating cells in a jejunal crypt of neonatal piglets was near 50%, and then the proportion was decreased by 17% on d 18 of lactation. In addition, weaning stress is shown to negatively influence physiological functions and morphology of enterocytes in nursey pigs, causing increased apoptosis, proliferation, and differentiation that are critical in recovery, development, maintenance of intestinal epithelium [89][90][91].…”
Section: Enterocyte Proliferation In Nursery Pigsmentioning
confidence: 99%
“…Thus, crypt cell proliferation has been used as a marker showing the status of intestinal maturation, development, or maintenance of pigs. According to Jang et al [88], the proportion of proliferating cells in a jejunal crypt of neonatal piglets was near 50%, and then the proportion was decreased by 17% on d 18 of lactation. In addition, weaning stress is shown to negatively influence physiological functions and morphology of enterocytes in nursey pigs, causing increased apoptosis, proliferation, and differentiation that are critical in recovery, development, maintenance of intestinal epithelium [89][90][91].…”
Section: Enterocyte Proliferation In Nursery Pigsmentioning
confidence: 99%
“…All these results indicate that Zn-, Cu-and Mn-MHAC can greatly improve the production e ciency of the LY 1st parity sows compared with amino acid chelated (AAC) trace element which is consistent with previous reports on sows, piglets, broilers, cows and other animals which made comparison between methionine hydroxy analogue chelate (MHAC) and inorganic trace elements. A similar study of sows showed that sows fed Cu-, Zn-and Mn-MHAC affects the intestinal health of fetuses and piglets, promotes the development of skeletal muscle to improves the growth performance of offspring [27]. Cu-MHAC even 50% Cu-, Zn-, Mn-MHAC substitution also signi cantly increased feed intake and weight gain of piglets, resulting in better muscle development [27,42].…”
Section: Discussionmentioning
confidence: 93%
“…A similar study of sows showed that sows fed Cu-, Zn-and Mn-MHAC affects the intestinal health of fetuses and piglets, promotes the development of skeletal muscle to improves the growth performance of offspring [27]. Cu-MHAC even 50% Cu-, Zn-, Mn-MHAC substitution also signi cantly increased feed intake and weight gain of piglets, resulting in better muscle development [27,42]. In addition, Zn-MHAC improved milk production and signi cantly inhibited the in ammatory response of udder [43].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The concentration of TNF-α was measured in serum and mucosa samples using the Porcine TNF-α Immunoassay Kit (#PTA00; R&D Systems, Minneapolis, MN, USA) as previously described by Holanda and Kim [24]. The concentration of protein carbonyl was measured using the OxiSelect Protein carbonyl ELISA Kit (Cell Biolabs, Inc., San Diego, CA, USA) as previously described by Jang et al [25].…”
Section: Immune and Oxidative Stress Statusmentioning
confidence: 99%